Congenital ossicular chain malformations with mobile stapes in children: Results in 17 cases. (23rd December 2015) - Vincent, Robert; Wegner, Inge; Derks, Laura S. M.; Grolman, Wilko
Abstract : Objectives/Hypothesis: To prospectively evaluate surgical findings and hearing results in children undergoing surgery for congenital malformations of the ossicular chain with a mobile stapes footplate (Teunissen and Cremers class III malformations). Study Design: A nonrandomized, nonblinded, prospective case series. Methods: Fifteen consecutive pediatric patients who underwent 17 surgical procedures for congenital ossicular malformations with a mobile stapes at a tertiary referral center were included. In 16 cases, postoperative pure‐tone audiometry was available. The surgical technique for repair of the ossicular chain was dictated by the surgical findings at the time of surgery. The majority of the cases underwent ossiculoplasty. A Teflon piston, partial ossicular replacement prosthesis, or total ossicular replacement prosthesis was used in these cases. Associated surgical techniques included malleus relocation, Silastic banding, drilling out of a bony bridge, and a combination of these techniques. Hearing loss was evaluated using preoperative and postoperative four‐frequency (0.5, 1, 2, and 4 kHz) audiometry. Air‐conduction thresholds, bone‐conduction thresholds, and air‐bone gaps were measured. Postoperative audiometry was performed at 3, 6, 9, 12, 18, and 24 months after surgery and at a yearly interval thereafter. Results: Overall, a postoperative air‐bone gap closure to 10 dB or less was achieved in 63% of the included cases. A postoperative air‐bone gap closure to 20 dB or less was achieved in 75%. Postoperative sensorineural hearing loss did not occur in any of the cases. Conclusions: Ossicular reconstruction is a feasible treatment option in children with congenital malformations of the ossicular chain with a mobile stapes footplate. Level of Evidence: 4. Laryngoscope, 126:682–688, 2016